Figure-Ground Processing: A Reassessment of Gelb and Granit. (March 2018) - Nelson, Rolf; Hebda, Nicholas
In 1923, Adhemar Gelb and Ragnar Granit, two prominent researchers in early Gestalt perceptual theory, reported a lower threshold for detection of a target (a small colored dot) on the ground region of an image than on an adjacent figural region. Although their results had a wide influence on the understanding of figure-ground perception, they are at odds with more recent investigations in which figural regions appear to have a processing advantage over ground regions. The two present studies replicated Gelb and Granit's experiment using a similar figure-ground stimulus albeit with a two-alternative forced choice procedure rather than their original method of adjustment. Experiment 1 found that, contrary to Gelb and Granit's findings, a detection advantage was found for the figural over the ground region. Experiment 2 indicated that explicit contours might have played a role in detection.